Regulationist Macro-Models for Developing Countries. An Application to the Argentine New Development Pattern - Demian Tupac Panigo; Pablo Ignacio Chena (Revue de la Régulation)
In this paper we present a regulationst structural macroeconometric model (RSMM) to develop economic forecasts and examine different policy outcomes in Argentina. RSMM main characteristics involve cumulative causation dynamics where income distribution, macroeconomic volatility, credit rationing and productive heterogeneity conjugates to obtain a new instrument to precisely examine key macroeconomic and social variables. Available empirical results indicates: 1) the existence of dynamic increasing returns to scale; 2) the relevance of income distribution for investment, tax collection and public expenditures; 3) the significant influence of macroeconomic volatility on employment generation; 4) the strong effect of investment (positive) on imports and domestic consumption (negative) on exports; and 5) that price dynamics depends on wages and demand factors but also (and predominantly) on external variables and income policies.